Effectiveness of iron-based phosphate binders in reduction of hyperphosphataemia in chronic kidney disease patients - Pokhrel, Anil; Chand, Hema; K.C., Prabal; Shrestha, Nilasma; Ghimire, Pradeep; Ghimire, Pravesh; Adhikary, Laxman Prasad (Journal of Kathmandu Medical College, 2023)
Background: Ferric citrate is novel iron-based phosphate-binding drug for management of hyperphosphataemia and iron-deficiency anaemia in chronic kidney disease (CKD) patients.Objectives: To evaluate impact of ferric citrate therapy on reduction of phosphate levels and improvement in haematological parameters in CKD stages 3-5.Methods: This analytical, observational study was conducted at Kathmandu Medical College Teaching Hospital from 2020 July-December after ethical clearance using convenience sampling method. Non-dialysis dependent patients at CKD stages 3-5, having hyperphosphataemia (serum phosphate >=4.6mg/dL) and anaemia (serum haemoglobin